Identification of conserved and tissue-restricted transcriptional profiles for lipid associated macrophages - Yingzheng Xu; Hannah Hillman; Michael Chang; Fanta Barrow; Stoyan Ivanov; Xavier S. Revelo; Jesse W. Williams (Communications Biology)
Abstract Macrophages are essential immune cells in all tissues and are vital for maintaining tissue homeostasis, immune surveillance, and immune responses. Considerable efforts have identified shared and tissue-specific gene programs for macrophages across organs during homeostasis. This information has dramatically enhanced the understanding of tissue-restricted macrophage programming and function. However, few studies have addressed the overlapping and tissue-specific responses of macrophage subsets following inflammation. One subset of macrophages observed across several studies, lipid-associated macrophages (LAMs), have gained interest due to their unique role in lipid metabolism and potential as a therapeutic target. LAMs are associated with regulating disease outcomes in metabolically related disorders including atherosclerosis, obesity, and metabolic dysfunction-associated steatotic liver disease. We utilized single-cell RNA sequencing datasets to profile LAM diversity across multiple tissues and inflammatory conditions in mice and humans, to define a shared LAM transcriptional profile, including Trem2 and Lpl, and sets of tissue-specific gene programs. Importantly, LAM markers were highly conserved with human LAM populations that emerge in inflammation. Overall, this analysis provides a detailed transcriptional landscape of tissue-restricted and shared LAM gene programs, data that may help instruct appropriate molecular targets for broad or tissue-restricted therapeutic interventions to modulate LAM populations in disease.